Developing Inquiry-Based Learning Modules to Enhance Critical Thinking: A Study on “My Indonesia is Rich” Social Studies Material - Hariani, Alfiah; Yusnaldi, Eka (Journal of Social Work and Science Education, 2025)
This study aims to develop and test the effectiveness of an Inquiry-Based Learning (IBL) module for the topic “My Indonesia is Rich” in enhancing critical thinking skills among fifth-grade students at Madrasah Ibtidaiyah. Employing Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the module underwent rigorous validation by material, media, and language experts, achieving an average score of 4.00 (very good category). Effectiveness was tested via pretest-posttest assessments involving 20 students. The module significantly improved critical thinking, with average scores rising from 52.50 (pretest) to 83.25 (posttest) and an N-Gain of 0.65 (medium–high category). Student feedback yielded an average score of 68.5/80 (very good), confirming the module’s usability and appeal. This study pioneers an IBL-based module tailored to Madrasah Ibtidaiyah’s social studies curriculum, bridging pedagogical innovation with cultural relevance in Indonesian elementary education. The validated module offers teachers a ready-to-use, contextual tool to foster active, meaningful learning aligned with madrasa students’ needs. The research provides an evidence-based model for developing IBL materials that enhance critical thinking while preserving local cultural context, applicable to similar educational settings.